Luteolin targets MKK4 to attenuate particulate matter-induced MMP-1 and inflammation in human keratinocytes - Jaehyeok Yun; Jong-Eun Kim (Scientific Reports)
Abstract Particulate matter (PM) is an environmental pollutant that causes premature skin aging and inflammation. In the present study, we investigated the protective effects of luteolin, a bioactive flavonoid, against PM-induced skin damage in human keratinocytes (HaCaT cells). We examined the antioxidant and anti-inflammatory properties of luteolin, focusing on its ability to inhibit key markers of skin aging and inflammation, specifically matrix metalloproteinase-1 (MMP-1) and cyclooxygenase-2 (COX-2). The results demonstrated that luteolin effectively suppressed PM-induced MMP-1 and COX-2 expression and reduced the production of the proinflammatory cytokine IL-6. Mechanistically, luteolin inhibited the activation of AP-1 and NF-κB pathways and decreased reactive oxygen species (ROS) levels in HaCaT cells. Additionally, luteolin binds directly to mitogen-activated protein kinase kinase (MKK) 4, inhibiting its kinase activity and subsequently reducing the phosphorylation of JNK1/2 and p38 mitogen-activated protein kinase. These findings suggest that luteolin can mitigate PM-induced skin aging and inflammation through multiple molecular pathways, highlighting its potential as a therapeutic agent to protect skin health.